Pengembangan Instrumen Evaluasi pada Praktikum Uji Enzim Katalase di SMA Negeri Titian Teras Muaro Jambi - M. Erik Sanjaya; Rayandra Asyhar; Bambang Hariyadi (Edu-Sains: Jurnal Pendidikan Matematika dan Ilmu Pengetahuan Alam, 2015)
The requirement for evaluation instruments learning outcomes authentically need to be done to get description totality about the student competence, when carry out biology experiment activity on katalase enzyme subject matter. This sudy aims to produce the final product in the form of an evaluation instrument for catalase enzyme experiment test. Development model adopted in this study is ADDIE model. Based on the results of expert judgement, the instrument was valid and can be tested in classroom. The results of the expert validation, evaluation instrument found that the enzyme catalase experiment test has appropriated entirety, in terms of the content aspect, constructs, linguistic, and practicalities. The test results were showed that the instrument has high realiability and validity for all student competency. Therefore, the conclusion is this evaluation instrument theority and rasionally that good and valid to use for measuring and considering all student competency for catalase enzyme experiment test.